Surface morphologies and corresponding hardness evolution during nanoscratching - Shuohua Zhang (Journal of Materials Research and Technology, 2020)
Machining surface topography is a key factor affecting the properties of optical materials. It is generally accepted that the fracture mode tends to dominate practical concerns on machined parts and the elastic recovery area decreases with the increase of normal load. However, material removal rate is low for ductile zone processing of brittle materials. In this case, pile-up and elastic recovery are key factors for surface quality. In this study, an accurate scratching and ploughing hardness model with consideration of both pile-up and elastic recovery was established based on a series of continuous and constant nanoscratch tests. The hardness evolution mechanism under different nanoscratch deformation modes was then investigated. It was found that, in different modes, hardness values exhibited different characteristics due to the change of elastic recovery rate and the intersection of elastic and plastic states. Further, the mapping relationship between hardness dispersion and surface morphology characteristics was also investigated. The results indicated that high degree of hardness dispersion usually corresponded to modes Ⅰ and Ⅱ while stable hardness value represented a steady plastic stage. Based on the intrinsic relationship between evolution of hardness and deformation modes, predicting hardness distribution by in-situ testing data and then adjusting deformation mode in real time would be helpful in optimizing surface quality.